Lectotypification of the name Agrostis ventricosa Gouan (Poaceae) - Scoppola, Anna; Banfi, Enrico (Phytotaxa, 2021)
Gastridium ventricosum (Poaceae) is the currently accepted name of Gouan’s Agrostis ventricosa, whose previous unclear type designation is briefly discussed and superseded. All relevant sources, specimens, illustrations, and the author’s relevant correspondence are carefully evaluated, the original material and possible type specimens are thoroughly discussed for the purpose to fix the precise taxonomic application of the name. We have chosen as the best admissible lectotype a newly discovered, well-preserved specimen enclosed in a letter sent by Antoine Gouan to Carl Linnaeus in 1761. This letter, Ref. L2998, is preserved in the Linnean Society of London’s collections (LINN) and was drawn up a year before the publication of the species name.